(untitled) - Richard J Trudeau (New York, 1993)
The book offers a stimulating excursion into pure mathematics. It leads from simple graphs through planar graphs, Euler's formula, Platonic graphs, coloring, the genus of a graph, Euler walks and Hamilton walks. Finally, it concludes with a discussion of The Seven Bridges of Kõnigsberg, with which Euler opened up the field of graph theory
Keywords: graph theory